ANALYSIS OF FINANCIAL PERFORMANCE AND SHARE PERFORMANCE BEFORE AND AFTER COVID-19 PANDEMIC ON THE INDONESIA STOCK EXCHANGE (IDX) - Andini, Rita; Dheasey Amboningtyas (Jurnal Ekonomi, 2022)
The purpose of this study was to see whether there were differences in the financial performance and stock performance of companies listed on the Indonesia Stock Exchange (IDX) before and after the Covid-19 pandemic. Companies listed on the Indonesia Stock Exchange at least make up the research population. The sample of this study amounted to 487 companies. Research data were collected through purposive sampling. The results showed that the variables of liquidity ratios, profitability ratios, solvency ratios, and activity ratios had significant differences. Between before and after the Covid-19 pandemic, the liquidity ratio (current ratio), profitability ratio (return on assets), and activity ratio (asset turnover) all decreased. Meanwhile, the solvency ratio (debt to equity) all increased.